Rabi oscillations and quantum beats in a qubit in distorted magnetic field - Ivanchenko, E.A.; Tolstoluzhsky, A.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
In a two-level system the time-periodic modulation of the magnetic field stabilizing the magnetic resonanceposition has been investigated. It was shown that the fundamental resonance is stable with respect to consistent variation of the longitudinal and transverse magnetic fields. The time-dependency of the Rabi oscillationsand quantum beats of the spin flip probability was numerically researched in different parameter regimes taking into account dissipation and decoherence in the Lindblad form. The present study may be useful in the analysis of interference experiments and for manipulation of quantum bits.